A CFD simulation on effects of methane/biogas ratio on 2-stroke free-piston linear engine’s scavenging
<span data-sheets-value=""1":2,"2":"On the work of investigating the effect of methane percentage in biogas on the two-stroke free-piston linear engine (FPLE) power output, a scavenging simulation implementation is required. Although the computational fluid dynamics (CFD) method was recognized as an effective solution, the result may, however, be not precise if the boundary conditions and the gas properties are determined inaccurately. This paper represents a CFD scavenging simulation, in which, a zero-dimensional model for the unsteady flow into the bounce-chamber based on Reynolds transport theorem was built to observe the scavenging’s boundary conditions. Simultaneously, the mixture characteristics following methane percentage and temperature are also estimated, in which, 5 circumstances of biogas component: 40% CH_4, 50% CH_4, 60% CH_4, 70% CH_4, and 100% CH_4 that will be inputted in CFD modeling afterward. The result shows that although delivered gas mass enhanced when using low %CH_4 biogas, the volumetric efficiency is decreased, particularly from 0.679 to 0.612 when %CH_4 vary from 100% to 40% at engine frequency f=50Hz."" data-sheets-userformat=""2":14783,"3":"1":1,"4":"1":2,"2":16370588,"5":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"6":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"7":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"8":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"10":0,"11":4,"14":"1":3,"3":1,"15":"Calibri","16":11">On the work of investigating the effect of methane percentage in biogas on the two-stroke free-piston linear engine (FPLE) power output, a scavenging simulation implementation is required. Although the computational fluid dynamics (CFD) method was recognized as an effective solution, the result may, however, be not precise if the boundary conditions and the gas properties are determined inaccurately. This paper represents a CFD scavenging simulation, in which, a zero-dimensional model for the unsteady flow into the bounce-chamber based on Reynolds transport theorem was built to observe the scavenging’s boundary conditions. Simultaneously, the mixture characteristics following methane percentage and temperature are also estimated, in which, 5 circumstances of biogas component: 40% CH_4, 50% CH_4, 60% CH_4, 70% CH_4, and 100% CH_4 that will be inputted in CFD modeling afterward. The result shows that although delivered gas mass enhanced when using low %CH_4 biogas, the volumetric efficiency is decreased, particularly from 0.679 to 0.612 when %CH_4 vary from 100% to 40% at engine frequency f=50Hz. , number=4, journal=Journal of Technical Education Science, author=Ho , Van Phuc and Nguyen , Huynh Thi and Huynh , Thanh Cong and Nguyen , Van Trang, year=2020, month=Aug., pages=130–139